Why no one speaks about "˜classic´ bibliographic databases? - Giménez-Toledo, Elea; Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2012)
The role of specialized bibliographic databases in the current environment of online information search dominated by search engines and large multidisciplinary databases is described. The databases usefulness for searching specialized information and the need for intermediation of the resource centres for research are discussed.